2000
DOI: 10.1164/ajrccm.161.3.9901113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dopexamine-induced Increase in Cardiac Index on Splanchnic Hemodynamics in Septic Shock

Abstract: In 12 patients with hyperdynamic septic shock we studied the effect of dopexamine, a combined dopamine and beta-adrenergic agonist, on hepatosplanchnic hemodynamics and O(2) exchange. All patients required noradrenaline to maintain mean arterial pressure > 60 mm Hg (noradrenaline >/= 0.04 microg x kg(-1) x min(-1)) with a cardiac index >/= 3.0 L/min/m(2). Splanchnic blood flow (Qspl) was measured using primed continuous infusion of indocyanine green dye with hepatic venous sampling. In addition tonometric gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 33 publications
0
16
0
4
Order By: Relevance
“…However, individual values were not presented. A study by Kiefer et al [6] on the effects of dopexamine clearly showed that fractional splanchnic blood flow in some patients had obviously changed between baseline and the subsequent control value. In six patients Reinelt et al [7] presented individual data on splanchnic O 2 delivery and O 2 consumption which obviously show considerable changes between baseline and control in some patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, individual values were not presented. A study by Kiefer et al [6] on the effects of dopexamine clearly showed that fractional splanchnic blood flow in some patients had obviously changed between baseline and the subsequent control value. In six patients Reinelt et al [7] presented individual data on splanchnic O 2 delivery and O 2 consumption which obviously show considerable changes between baseline and control in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…tients has been assessed only by comparing baseline and control measurements after therapeutic interventions [6,7]. In this study we examined the variability of splanchnic blood flow during a 4-h period of unchanged global hemodynamics in eight patients with sepsis.…”
mentioning
confidence: 99%
“…Son intérêt dans le choc septique résiderait dans sa capacité à optimiser les pressions de perfusion rénale et splanchnique, bien que cette hypothèse soit remise en question dans plusieurs travaux récents (34). Elle pourrait ainsi, en association avec les vasoconstricteurs majeurs, contrebalancer les eff ets néfastes de l'adréna-line et de la noradrénaline sur la perfusion périphérique (35).…”
Section: Dopexamineunclassified
“…So konnte gezeigt werden, dass eine eingeschränkte Leberfunktion bei Patienten nach schwerem Trauma anhand einer verringerten ICGClearance sicher erkannt wird, wobei bei diesen Patienten ursächlich eine Verringerung der ICG-Extraktion und nicht eine Minderperfusion der Leber vorlag (20). Darüber hinaus ist bekannt, dass die ICG-Clearance mit der Überlebensrate kritisch kranker Patienten einer operativen Intensivstation korreliert (35). Bereits zwei Tage vor Verlegung bzw.…”
Section: Monitoringunclassified
“…In den letzten Jahren konnte gezeigt werden, dass davon ausgegangen werden muss, dass ein erniedrigter pH i bzw. ein erhöhter pCO 2 der Magenmukosa im Sinne einer lokalen Azidose aufgrund einer eingeschränk-ten CO 2 -Auswaschung interpretiert werden muss, und somit in erster Linie ein Indikator für eine mukosale Minderperfusion ist (35,69,82 …”
Section: Monitoringunclassified